2016
DOI: 10.1111/jdi.12460
|View full text |Cite
|
Sign up to set email alerts
|

Serum homocysteine level and gestational diabetes mellitus: A meta‐analysis

Abstract: Aims/IntroductionHomocysteine levels during pregnancy in women with gestational diabetes mellitus (GDM) have been studied; however, it remains unclear whether hyperhomocysteinemia is a useful predictor of insulin resistance. The present study aimed to evaluate the relationship between homocysteine level and GDM.Materials and MethodsPubMed, Elsevier, Web of Science and CNKI were searched for relevant studies published up to January 2015. Manual searches of references of the relevant original studies were carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 36 publications
4
34
1
Order By: Relevance
“…The evidence was more consistent among women in the second trimester and for women older than 30 years of age. As a result of physiological decreases in albumin during pregnancy, as well as in association with folic acid supplementation, the serum concentrations of homocysteine decrease during pregnancy [19,20]. Surprisingly, in our study, we did not find significant differences in those results between the GDM and control groups.…”
Section: Discussioncontrasting
confidence: 85%
“…The evidence was more consistent among women in the second trimester and for women older than 30 years of age. As a result of physiological decreases in albumin during pregnancy, as well as in association with folic acid supplementation, the serum concentrations of homocysteine decrease during pregnancy [19,20]. Surprisingly, in our study, we did not find significant differences in those results between the GDM and control groups.…”
Section: Discussioncontrasting
confidence: 85%
“…A recent meta-analysis examined the relationship between serum homocysteine concentration and GDM in ten eligible studies. The authors reported significantly higher homocysteine concentrations among women with GDM as compared with those without GDM [ 146 ]. B vitamins, including folic acid, B2, B6, and B12 are essential for homocysteine homeostasis, and this may be one reason why deficiencies and imbalances of these micronutrients are associated with GDM [ 147 ].…”
Section: Pathophysiology Of Gestational Diabetesmentioning
confidence: 99%
“…Gestational diabetes mellitus (GDM) is a metabolic complication with glucose intolerance during pregnancy. High plasma level of Hcy was found in pregnant women with GDM as compared to nonpregnant women with normal glucose tolerance (Gong et al., 2016). (Tarim et al., 2004) conducted a study to determine whether elevated plasma Hcy is associated with GDM in Turkish women and found that women with gestational diabetes with abnormal screening test results but normal oral glucose tolerance test results have higher Hcy levels than normal pregnant women.…”
Section: Cysteine and Homocysteine As Biomarker Of Various Diseasesmentioning
confidence: 99%